Agroterrorism in the U.S.: An Overview - Renée M. Goodrich Schneider; Keith R. Schneider; C. D. Webb; Mike Hubbard; Douglas L. Archer (EDIS)
Revised! FSHN-05-21, a 4-page fact sheet by R. Goodrich Schneider, K.R. Schneider, C.D. Webb, M. Hubbard, and D.L. Archer, discusses the use of biological agents in a deliberate, harmful attack, or terrorism using the weapons of biological warfare against the U.S. agricultural and food processing system. Includes references. Published by the UF Department of Food Science and Human Nutrition, April 2009.